2019
DOI: 10.15666/aeer/1705_1168711699
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Temporal and Spatial Variations of Water Quality and Water Level Changes in Poyang Lake Based on 5 Consecutive Years’ Monitoring

Abstract: Zheng et al.: Relationships between temporal and spatial variations of water quality and water level changes in Poyang Lake based on 5 consecutive years' monitoring -11687 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…From Figure 13, the Chl-a concentration of Poyang Lake is positively correlated with water temperature and water level. This finding is similar to the analysis of Zheng et al [37]. In the study area, summer is part of the wet season and, accordingly, the water level reached its yearly maximum in August 2015.…”
Section: Spatial and Seasonal Variation Of Chl-asupporting
confidence: 92%
See 1 more Smart Citation
“…From Figure 13, the Chl-a concentration of Poyang Lake is positively correlated with water temperature and water level. This finding is similar to the analysis of Zheng et al [37]. In the study area, summer is part of the wet season and, accordingly, the water level reached its yearly maximum in August 2015.…”
Section: Spatial and Seasonal Variation Of Chl-asupporting
confidence: 92%
“…On the other hand, the water level of Poyang Lake begins to decline in autumn, the water flow speed increases, and the The comparison in Figure 13 suggested that, regarding the spatial distribution of Chl-a, the highest concentrations of Chl-a in Poyang Lake are mainly distributed near the channel in the north of the lake, which connects it to the Yangtze River, in the places where the Ganjiang, Fuhe, Xinjiang, Raohe, and Xiushui rivers flow into the lake, and in the waters near to the shore of the lake. These observations can be attributed to the transport of various pollutants into the lake by the Ganjiang, Fuhe, Xinjiang, Raohe, and Xiushui rivers, and to human activities in waters near to the lake shore [37]. Sand mining occurs during the whole year in the northern channel that connects the lake with the Yangtze River [16].…”
Section: Spatial and Seasonal Variation Of Chl-amentioning
confidence: 99%
“…Overall, the water quality of Poyang Lake is the best during the wet period and the worst during the dry period (Li et al, 2020). Zheng et al (2019) monitored Poyang Lake from 2012 to 2016, and found that the total nitrogen concentration in the lake generally exceeded approximately 2.0 mg/L in winter and approximately 1.5 mg/L in spring and summer. They observed that the concentration of nitrogen and phosphorus were higher in the south and lower in the north.…”
Section: Effects Of Solute Source Locationmentioning
confidence: 99%